2017
DOI: 10.1186/s12882-017-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors and prevalence of microalbuminuria in HIV-infected patients: a cross-sectional analysis

Abstract: BackgroundRenal dysfunction is a common problem in the HIV+ population, due to the effect of both the HIV virus and the several classes of ARV drugs such as tenofovir (TDF). It is also known that the presence of renal damage correlates with cardiovascular risk and therefore with the risk of mortality of the patients accordingly. The detection of early renal damage is very important. Albuminuria and microalbuminuria are markers of early kidney disease and cardiovascular risk. The aim of the study is to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This finding suggested that albuminuria, which was associated with HIV, may be improved by ART as previously reported [59]. This finding agrees with a few studies which have shown the proportion of albuminuria to be high in persons with HIV [60,61].…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggested that albuminuria, which was associated with HIV, may be improved by ART as previously reported [59]. This finding agrees with a few studies which have shown the proportion of albuminuria to be high in persons with HIV [60,61].…”
Section: Discussionsupporting
confidence: 91%
“…Variable associations between fracture risk and low CD4 cell count (45,25) and HCV infection have been reported in previous studies (25,48). TDF use has been associated with higher risk of proteinuria (20,43,47) and fractures in several studies (49), while others failed to demonstrate such associations (45,25). Since the median TDF exposure at the index visit was only of 1 year we further examined the distribution of cumulative TDF use at visits after the index visit.…”
Section: Discussionmentioning
confidence: 85%
“…Consistent with data from prior studies (41), the prevalence of proteinuria observed in our cohort was higher in men with HIV compared to men without HIV (29% versus 6%). See comment in PubMed Commons below HIV-related kidney disease is multifactorial, resulting from direct HIV infection and damage of the renal epithelial cells (41-42), ARTrelated renal tubular toxicity (43)(44)(45), comorbidities such as HCV (46), diabetes mellitus or HTN, as well as low CD4 (47). In the multivariable analysis restricted to HIV+ men, proteinuria was associated with higher risk of fragility fracture independent of other HIVspecific and non-specific risk factors such as HTN and eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a detectable viral load is associated with a higher risk of MI [45]. However, biomarkers of inflammation and immune activation such as CRP, microalbuminuria, cystatin C and soluble CD14 are elevated in HIV-infected patients even when on cART [31,[46][47][48], reflecting residual inflammatory/immune activation. Consistent with these findings, we did not find any correlation between the evaluated parameters and viral load or CD4 count, suggesting that, after viral suppression, the detrimental factors leading to atherothrombotic events are not completely normalized, and may reflect the excess CV risk observed in HIV-infected patients even when successfully treated with ART [6,7,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Key demographic data (age, gender and nationality), clinical data [body mass index (BMI), year of HIV infection, presence of coinfection with hepatitis B or C virus (HBV/ HCV) and Centers for Disease Control and Prevention (CDC) category], viroimmunological data [CD4 count and HIV RNA, measured using polymerase chain reaction (PCR)], and therapeutic and laboratory data (hepatic and renal function, glucose concentration and lipid profile) were assessed in all subjects. Microalbuminuria was measured on single-day urine samples using particle-enhanced immunonephelometric assays (BN II System; Siemens Healthcare Diagnostics, Inc., NY, USA) [31]. The groups were homogeneous for gender and CDC classification.…”
Section: Study Populationmentioning
confidence: 99%